2009
DOI: 10.1093/hmg/ddp392
|View full text |Cite
|
Sign up to set email alerts
|

Mice defective in Trpm6 show embryonic mortality and neural tube defects

Abstract: The syndrome of hypomagnesemia with secondary hypocalcemia is caused by defective TRPM6. This protein is an ion channel that also contains a kinase in its C-terminus. It is usually diagnosed in childhood and, without treatment with supplemental Mg, affected children suffer from mental retardation, seizures and retarded development. We developed a mouse lacking Trpm6 in order to understand in greater detail the function of this protein. In contrast to our expectations, Trpm6(-/-) mice almost never survived to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
81
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 44 publications
6
81
1
2
Order By: Relevance
“…Heterozygous TRPM6 þ / À mice exhibit mild hypomagnesemia under a normal diet as an indication of a milder phenotype associated with the loss of one TRPM6 allele. 33,34 Still, the observed difference in serum Mg 2 þ values in these mice is rather low although significant. 33,34 Moreover, the heterozygous deletion of TRPM6 results in unaffected Mg 2 þ urinary excretion when compared with WT under normal Mg 2 þ diet.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Heterozygous TRPM6 þ / À mice exhibit mild hypomagnesemia under a normal diet as an indication of a milder phenotype associated with the loss of one TRPM6 allele. 33,34 Still, the observed difference in serum Mg 2 þ values in these mice is rather low although significant. 33,34 Moreover, the heterozygous deletion of TRPM6 results in unaffected Mg 2 þ urinary excretion when compared with WT under normal Mg 2 þ diet.…”
Section: Discussionmentioning
confidence: 79%
“…33,34 Still, the observed difference in serum Mg 2 þ values in these mice is rather low although significant. 33,34 Moreover, the heterozygous deletion of TRPM6 results in unaffected Mg 2 þ urinary excretion when compared with WT under normal Mg 2 þ diet. 33 In contrast to this situation in mice, measured serum Mg 2 þ values from parents in our study are normal (data not shown), indicating that heterozygous humans are asymptomatic and have no significant change in Mg 2 þ metabolism, not supporting the idea of a milder phenotype in humans.…”
Section: Discussionmentioning
confidence: 79%
“…I am not aware of a TRPM6 knockout mouse model that is not an embryonic lethal. 68 The human patient data suggest hypocalcemia and possibly hypercalciuria are caused by parathyroid gland failure induced by hypomagnesemia. When there is hypercalciuria, the risk of developing kidney stones will be higher.…”
Section: Questions and Answersmentioning
confidence: 99%
“…Those that survive display massive neural tube closure defects. 103 Interestingly, plasma Mg 2ϩ levels are lower in TRPM6 ϩ/Ϫ as compared with TRPM6 ϩ/ϩ mice. In contrast to HSH, high-Mg 2ϩ diet does not prevent mortality in TRPM6-null embryos.…”
Section: Role Of Trpm6 Channels In Renal Magnesium Homeostasismentioning
confidence: 97%
“…101,102 The recent description of a TRPM6-deficient mouse model adds yet another level of complexity. 103 The absence of TRPM6 gives rise to a different phenotype in mice than in humans. In contrast to previous expectations, the majority of TRPM6 Ϫ/Ϫ mice die at approximately day 12.5.…”
Section: Role Of Trpm6 Channels In Renal Magnesium Homeostasismentioning
confidence: 99%